2018
DOI: 10.1016/j.juro.2018.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Pain is Independent of Stone Burden and Predicts Surgical Intervention in Patients with Ureteral Stones

Abstract: PROMIS pain scores are independent of stone size and location. Attention to emergency department discharge symptom control offers the potential to improve patient care. PROMIS pain intensity is an independent predictor of surgical intervention in patients with ureteral stones 1 cm or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…11 However, Jennifer et al studied 650 patients with ureteral stones and found no significant correlation between stone size, localization, or pain severity. 12 In our study, while the size of the ureteral stones increased in correlation with the VAS pain score, this correlation was not seen for renal stones ( r =0.34 p < 0.001, r =–0.027, p = 0.64). In the comparison of stone localization and pain severity, while the distal ureteral stones were the most painful (VAS score 10 cm), the decrease in pain intensity was listed as proximal (VAS score 8.5 cm) - middle ureter (VAS score 7.7 cm) ( p < 0.001).…”
Section: Discussioncontrasting
confidence: 58%
“…11 However, Jennifer et al studied 650 patients with ureteral stones and found no significant correlation between stone size, localization, or pain severity. 12 In our study, while the size of the ureteral stones increased in correlation with the VAS pain score, this correlation was not seen for renal stones ( r =0.34 p < 0.001, r =–0.027, p = 0.64). In the comparison of stone localization and pain severity, while the distal ureteral stones were the most painful (VAS score 10 cm), the decrease in pain intensity was listed as proximal (VAS score 8.5 cm) - middle ureter (VAS score 7.7 cm) ( p < 0.001).…”
Section: Discussioncontrasting
confidence: 58%
“…Pain intensity and interference were also measured with individual PROMIS instruments, allowing for comparison with population norms. Recently, PROMIS measures have been used to characterize stone patients in various settings [ 18 20 ]. In our study, we noted consistency among instruments in ascertaining peak symptoms, the evolution of daily symptoms, and the heterogeneity of the lived experiences following URS and stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, a study by Gourlay et al did not find any association between the severity of pain and the need for hospitalisation or rescue intervention within 60 days [ 11 ]. A study by Portis et al found that pain severity was an independent predictor of the need for surgical intervention [ 13 ]. However, a study by Innes et al found that early intervention resulted in higher rates of emergency department revisits and rehospitalization [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gourlay et al and Splinter et al reported that there was no significant correlation of pain with stone size, location, and patient outcomes. On the other hand, Portis et al in a study found that pain score was an independent predictor of surgical outcome [ 11 - 13 ]. However, a study by Sasmaz and Kirpat found a significant correlation of pain severity with hydronephrosis and biomarkers like C-reactive protein and Neutrophil-Lymphocyte ratio [ 10 ].…”
Section: Introductionmentioning
confidence: 99%